Produção e caracterização de filmes de poli (3-hidroxibutirato) (PHB) com alginato de sódio esterificado e poli (etileno glicol) (PEG) - Lopes, Jamilly Ribeiro (2016)
Alternative materials have long been studied and developed to replace conventional skin dressings due to the emergence of new biopolymers and development of new polymeric film fabrication techniques. As a new material for polymeric dressings, films of poly (hydroxybutyrate) (PHB) blended with esterified alginate (ALG-e) and Poly (ethyleneglycol) were studied. The esterification of sodium alginate (ALG-e) generated a material with some amphiphilic characteristics and increased its compatibility with the PHB. PEG was added as plasticizer in PHB/ALG-e films, since PEG is often used in blends with PHB to improve its flexibility and reduce its hydrophobicity. At the amounts studied, it was found that both PEG and ALG-e increase the degree of crystallinity, but a decrease in the hydrophobic nature of PHB films was observed. At the maximum concentration of ALG-e and PEG used an increase in water vapor permeability and a decrease in tensile strength was reached due to the synergistic effect caused by better homogenization of PEG and ALG-e in the PHB matrix.